Descriptions of Clothes in the English-language Publicistic Discourse of the 21st Century - Marchenko , Nataliia (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
The article explores the phenomenon of descriptions of clothes in the English-language publicistic discourse of the 21st century as an important object of contemporary linguistics and media studies. The relevance of this research is determined by the increasing role of mass media in shaping public opinion and cultural codes, where descriptions of clothes perform not only an informative function but also evaluative, social-identification, and symbolic functions. In the 21st century, fashion emerges as a semiotic system reflecting social transformations, ideological priorities, and globalization processes, which heightens the scientific interest in the analysis of linguistic means of representation. The purpose of the study is to identify lexical, stylistic, and discursive features of descriptions of clothes in English-language publicistic texts and to determine their communicative functions in the modern media space. The research methods combine content analysis, linguistic-stylistic analysis, and elements of discourse analysis. The empirical base includes texts from English-language publications (“The Guardian”, “The New York Times”, “Vogue”, “The Independent”) reflecting contemporary socio-cultural processes. The results demonstrate that descriptions of clothes function as a multifunctional tool: they represent characters’ appearance, emphasize social status, convey cultural trends, and realize the evaluative-expressive potential of publicistic discourse. The study’s theoretical significance lies in deepening knowledge about the functioning of fashion language in media, while its practical significance is determined by the potential interdisciplinary application in linguistics, cultural studies, and media studies. In conclusion, descriptions of clothes are an important means of meaning-making in contemporary English-language media, as they reflect fashion changes and shape social perceptions of norms, gender roles, status, and ideals of beauty, thus contributing to the construction of 21st-century discourse.